Identification of refined petroleum products in contaminated soils using an identification index for GC chromatograms - Kwon, Dongwook; Ko, Myoung-Soo; Yang, Jung-Seok; Kwon, Man Jae; Lee, Seung-Woo; Lee, Seunghak (SPRINGER HEIDELBERG, 2015)
Hydrocarbons found in the environment are typically characterized by gas chromatography (GC). The shape of the GC chromatogram has been used to identify the source of petroleum contamination. However, the conventional practice of simply comparing the peak patterns of source products to those of environmental samples is dependent on the subjective decisions of individual analysts. We have developed and verified a quantitative analytical method for interpreting GC chromatograms to distinguish refined petroleum products in contaminated soils. We found that chromatograms for gasoline, kerosene, and diesel could be divided into three ranges with boundaries at C-6, C-8, C-16, and C-26. In addition, the relative peak area (RPA(GC)) of each range, a dimensionless ratio of the peak area within each range to that of the total range (C-6-C-26), had a unique value for each petroleum product. An identification index for GC chromatograms (IDGC), defined as the ratio of RPAGC of C-8-C-16 to that of C-16-C-26, was able to identify diesel and kerosene sources in samples extracted from artificially contaminated soils even after weathering. Thus, the IDGC can be used to effectively distinguish between refined petroleum products in contaminated soils.
Keywords: POLYCYCLIC AROMATIC-HYDROCARBONS; PRESTIGE OIL-SPILL; HEAVY FUEL-OIL; CRUDE OILS; BIODEGRADATION; PAHS; GC/MS